Localization solution for underwater robots using low-cost single-beam SONAR and IMU - Kong, Ze Jie (Nanyang Technological University, 2023)
This project proposes an underwater robot localization system that utilizes low-cost SONAR and IMU sensors to estimate a robot's position in an underwater environment. The proposed system leverages the ability of SONAR to measure distance and detect obstacles in the robot's surrounding environment, while IMU provides information about the robot's orientation and acceleration. By fusing the data from both sensors, the proposed system aims to provide a more accurate and robust localization solution compared to using either sensor in isolation. The project includes the implementation of appropriate algorithms for sensor data processing, sensor fusion, and position estimation. The effectiveness of the proposed system will be evaluated through experimental testing in a controlled underwater environment. The expected outcome of this project is a low-cost underwater robot localization system that can be used for various underwater applications such as underwater exploration, environmental monitoring, and pipeline inspection.